Postpartum Retained Products of Conception: A Novel Approach to Follow-Up and Early Diagnosis - Smorgick, Noam; Krakov, Ayala; Maymon, Ron; Betser, Moshe; Tovbin, Josef; Pansky, Moty (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Purpose To investigate whether ultrasound follow-up for the detection of postpartum retained products of conception (RPOC) in women considered at risk for this condition may allow for early diagnosis.Methods Parturients at risk for RPOC underwent an ultrasound exam on the second postpartum day. Based on the ultrasound findings, women were either: (1) discharged to routine postpartum care in cases of normal scans, (2) invited for follow-up in cases of abnormal scans. We retrospectively analyzed the rates of women requiring uterine evacuation due to persistent abnormal scans.Results 761 parturients (out of 17 010 deliveries, 4.5 %) were included. Of those, 490 (64.4 %) women had a normal initial scan, but two of them were later readmitted for uterine evacuation. The remaining 271 (35.6 %) women were found to have an abnormal scan: (a) thickened endometrium > 10 mm with hypo- and hyper-echoes and negative Doppler flow considered low suspicion for RPOC was described in 260 cases, of whom 23 (8.8 %) underwent uterine evacuation with placental remnants confirmed in 12/23 (52.2 %), and (b) an echogenic mass with positive Doppler flow considered high suspicion for RPOC was described in 11 cases, all of whom underwent uterine evacuation, with placental remnants confirmed in 9/11 (81.8 %). The number of scans required to detect RPOC in one patient was 33.Conclusion Postpartum ultrasound evaluation may allow for early diagnosis of RPOC in women considered at risk for this condition.
Keywords: ultrasound; retained products of conception; residual trophoblastic tissue